Impacto da fibromialgia e fatores associados em uma população do sul do Brasil - Frantz, Patrícia Junges (2018)
Introduction: Fibromyalgia is a syndrome characterized by chronic central pain, fatigue, sleep disorders and depressive symptoms, which causes a great impact on patients' quality of life. The knowledge of the factors that may interfere with this impact may help to achieve an individualized therapy. Objective: To evaluate the impact of fibromyalgia and associated factors in women treated at the Policlínica Municipal de Palhoça Unisul (PMPU) in Santa Catarina. Methods: From Agust to December 2017, a cross-sectional epidemiological study was carried out withfibromyalgia patients who were asked to answer a self-administered questionnaire, which included sociodemographic data, life habits, clinical comorbidities, as well as validated instruments for the evaluation of anxiety (HADS-A, STAI-T and STAI-S) and depression (HADS-D and BDI), child abuse (CTQ) and domestic violence (WHO-VAW). The impact of fibromyalgia was assessed through FIQR-Br. The data were analyzed in the SPSS program, and the associations by Student's t-test and Pearson's correlation coefficient, with values of p <0.05 considered significant. Results: 51 patients participated in the research, with a mean age of 54.4 years. They were mostly married housewives with a family income of up to 3 minimum wages, not smokersneither alcohol consumers. Eighty percent were on pharmacological treatment and 20.6% on non-pharmacological therapy. Seventy percent related chronic comorbidities; 72.5 to 81.6% and 48 to 56.9% achieved scores compatible with anxiety and depression disorders, respectively. Twenty-four percent of patients had suffered severe physical abuse in childhood, and 34% reported having been sexually abused. Regarding domestic violence, 33% reported physical abuse, 47% psychological and 19.6% sexual abuse. The total FIQR-br was 67.33 ± 19.69. There was a positive correlation between HADS-A, HADS-D and BDI scores with all FIQR-Br domains. In the bivariate analysis by categories, there was a significant association of IDATE and BDI with all FIQ domains, and HADS-A and HADS-D with functional, symptom and total domains. Conclusion: The results demonstrate the high impact of fibromyalgia in patients treated at PMPU, as well as the high prevalence of anxiety and depressive symptoms, which are associated with a greater impact of the disease.